Differential Search Algorithm for Economic Dispatch with Valve-Point Effects - M. H., Sulaiman (2013)
This paper introduces a new method for determining the feasible optimal solution of Economic Dispatch (ED) problems which is using the recently developed Differential Search (DS) algorithm...